Christian Efing / Karl-Hubert Kiefer (Hg.): Sprachbezogene Curricula und Aufgaben in der beruflichen Bildung. Aktuelle Konzepte und Forschungsergebnisse - Prikoszovits, Matthias (Deutsch als Fremdsprache)
Keywords: Computer Science Applications; History; Education

Feed the Interface – Social-Media-Feeds als Schwellen - Schulz, Christian; Matzner, Tobias (Navigationen – Zeitschrift für Medien- und Kulturwissenschaften)

»The Filter is the Message« oder der entwendete Begriff - Zur Einführung - Schulz, Christian; Bäcker, Theresia; Kathöfer, Jasmin (Navigationen – Zeitschrift für Medien- und Kulturwissenschaften)

Filter(n) – Geschichte, Ästhetik, Praktiken (Navigationen – Zeitschrift für Medien- und Kulturwissenschaften)

›Sei was du willst, aber sei es richtig‹ Anforderungen zur Authentizität in Beauty Videos als Strategie flexibler Essentialisierung - Richter, Susanne (Geschlecht und Medien. Räume, Deutungen, Repräsentationen)
Mediale Darstellungen von Geschlecht und Sexualität sind eingebettet in Machträume und gesellschaftliche Ordnungen. Dieses Buch gibt Einblicke in kritische Analysen gegenwärtiger Mediennutzungs- und Deutungspraktiken. Außerdem setzt es sich mit der übergeordneten Frage auseinander, wie feministische und geschlechtertheoretische Zugänge für eine machtanalytische Weiterentwicklung der Medienforschung fruchtbar gemacht werden können.

Einleitung. Räume, Deutungen, Repräsentationen–über Verhältnisse von Geschlecht und Medien nachdenken - Hoffarth, Britta; Reuter, Eva; Richter, Susanne (Geschlecht und Medien: Räume, Deutungen, Repräsentationen)

Geschlecht und Medien. Räume, Deutungen, Repräsentationen
Mediale Darstellungen von Geschlecht und Sexualität sind eingebettet in Machträume und gesellschaftliche Ordnungen. Dieses Buch gibt Einblicke in kritische Analysen gegenwärtiger Mediennutzungs- und Deutungspraktiken. Außerdem setzt es sich mit der übergeordneten Frage auseinander, wie feministische und geschlechtertheoretische Zugänge für eine machtanalytische Weiterentwicklung der Medienforschung fruchtbar gemacht werden können.

Die Digitalisierung der Kreditwirtschaft. Computereinsatz in den Sparkassen der Bundesrepublik und der DDR, 1957-1991 - Schmitt, Martin (Newsletter der GWMT)

Computernutzung in der DDR. Die Geschichte des VVB Maschinelles Rechnen am Beispiel des Potsdamer Rechenzentrums - Schmitt, Martin (ZeitRäume 2020)
Keywords: DDR; VEB Maschinelles Rechnen; VVB Maschinelles Rechnen; Maschinelles Rechnen; 1950er-Jahre; Kombinat Datenverarbeitung

Aufbrüche in das Digitale Zeitalter. Computernutzung in Deutschland, 1951-1967 - Schmitt, Martin (Computer & Museum. Beiträge des Festkolloquiums vom 19.09.2020)
Keywords: DDR; VEB Maschinelles Rechnen; VVB Maschinelles Rechnen; Maschinelles Rechnen; 1950er-Jahre; Kombinat Datenverarbeitung

Rezension zu: Bernardo Bátiz-Lazo: Cash and Dash. How ATMs and Computers Changed Banking - Schmitt, Martin (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte)
Keywords: Wirtschaftsgeschichte; Bankengeschichte; Geldautomat; ATM; Geschichte; Technikgeschichte

Die Geschichte des Potsdamer Rechenzentrums: Sozialistische Computernutzung und die Digitalisierung in Ostdeutschland - Schmitt, Martin

Zinkoxid als photostabiler Luminophor zur optischen Sauerstoffdetektion - Poeplau, Michael; Ester, Stephan; Henning, Bernd; Wagner, Thorsten

Soziale Gesundheit als Bestandteil psychischer Gefährdungsbeurteilungen? - Kukuk, Marc; Sennefelder, Lisa; Kötting, Anna; Hundte, Horst-Walter (Journal Gesundheitsförderung für Akteurinnen und Akteure aus Politik, Wissenschaft und Praxis)

Sportsoziologie - Riedl, Lars (Sportwissenschaft - Themenfelder, Theorien und Methoden)

Sportsoziologie in 60 Minuten - Riedl, Lars
Der Band "Sportsoziologie in 60 Minuten“ führt kompakt in diesen Teilbereich der Sportwissenschaft ein. Er zeigt, mit welchen Phänomenen sich die Sportsoziologie beschäftigt und welche Themen aus ihrer Sicht relevant sind. Folgende Fragen werden geklärt: Wie ist die Sportsoziologie entstanden, wie hat sie sich bis zum heutigen Stand entwickelt und welche Verbindungen bestehen zu ihrer Mutterwissenschaft? Welche wissenschaftlichen Zielsetzungen und Aufgaben hat die Sportsoziologie und mit welchen Theorien nähert sie sich den für sie relevanten Phänomenen und Themen? Welchen Problem-/Fragestellungen widmet sie sich und welche Methoden kommen dabei typischerweise zum Einsatz? Der Band enthält Lernziele, Kontrollfragen und ein Beispiel aus der Praxis.
Keywords: Sportbeteiligung; Sportentwicklung; Sportsoziologie; Sportwissenschaft; Theorie-Praxis-Verhältnis

Einflüsse der Schulstrukturen auf das Gesundheitsverhalten der Lehrerlnnen - Meier, Heiko; Sennefelder, Lisa; Hundte, Horst-Walter (Journal Gesundheitsförderung für Akteurinnen und Akteure aus Politik, Wissenschaft und Praxis)

Teamtraining – Das Wissen ist in der Gruppe - Meier, Heiko; Sennefelder, Lisa; Hoost, Marika (Journal Gesundheitsförderung für Akteurinnen und Akteure aus Politik, Wissenschaft und Praxis)

[Vorwort] - Ried, Dennis (Welt-Ende, Gericht, neue Welt : Oratorium nach Worten der heiligen Schrift zumal der Offenbarung Johannis : op. 212 / Joachim Raff)

Explizierung und Implizierung von Konsekutivmarkern in Übersetzungen im Europarl-Korpus - Kunert, Irene Dorothea (Translation 4.0. Dolmetschen und Übersetzen im Zeitalter der Digitalisierung)

Komponieren für das Radio (Musiktheorie/Zeitschrift für Musikwissenschaft)
Keywords: radio

When Donors Turn into Acceptors: Ground and Excited State Properties of FeII Complexes with Amine-Substituted Tridentate Bis-imidazole-2-ylidene Pyridine Ligands - Vukadinovic, Yannik; Burkhardt, Lukas; Päpcke, Ayla; Miletic, Anabel; Fritsch, Lorena; Altenburger, Björn; Schoch, Roland; Neuba, Adam; Lochbrunner, Stefan; Bauer, Matthias (Inorganic Chemistry)
Keywords: Inorganic Chemistry; Physical and Theoretical Chemistry

A systematic approach to define flexibility in chemical engineering - Bruns, Bastian; Herrmann, Felix; Polyakova, Maria; Grünewald, Marcus; Riese, Julia (Journal of Advanced Manufacturing and Processing)
Abstract Increasing economic and environmental challenges leads to the need for changes in the chemical industry. In this context, a promising approach is utilizing flexible apparatuses and flexible plants to react to changing boundary conditions. However, the concept of flexibility in chemical engineering, which originated in manufacturing, still lacks a comprehensive organization and categorization of different types of flexibility. Thus, in this work, the origin of flexibility in manufacturing is traced, and a literature overview on flexibility in chemical engineering is provided. Based on a subsequent cluster analysis, four types of flexibility are identified and defined. Furthermore, this work enables research on flexibility to be integrated into a general and consistent definition of flexibility. The definitions are applied to examples from literature to achieve comparability. While enabling the qualitative assessment of flexibility, this work identifies open research gaps regarding the quantification of flexibility.
Keywords: General Medicine

Separation Units 4.0 – Trennapparate heute und morgen - Riese, Julia; Hoff, Andreas; Stock, Jürgen; Górak, Andrzej; Grünewald, Marcus (Chemie Ingenieur Technik)
Abstract Die chemische Industrie sieht sich mit gravierenden Herausforderungen konfrontiert: Die Einhaltung der Klimaschutzziele, die Auswirkungen der Energiewende und die zunehmende Bedeutung der Kreislaufwirtschaft treffen die gesamte Wertschöpfungskette. Lösungsansätze von der Prozess‐ über die Apparateebene bis hin zum Einzelphänomen sind notwendig, um die Wettbewerbsfähigkeit dieses zentralen Industriezweigs zu erhalten. In diesem Beitrag werden aktuelle Entwicklungen und zukünftige Handlungsfelder in der Trenntechnik, die für diese Herausforderungen wertvolle Beiträge leisten können, dargestellt.
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Transformable Decentral Production for Local Economies with Minimized Carbon Footprint - Pannok, Maik; Finkbeiner, Marco; Fasel, Henrik; Riese, Julia; Lier, Stefan (ChemBioEng Reviews)
Abstract Due to high energy‐intensive processes and a dependence on carbon‐based materials, the process industry plays a major role in climate change. Therefore, the substitution of fossil resources by bio‐based resources is indispensable. This leads to challenges arising from accompanying changes of the type, amount and location of resources. At the same time, transformable production systems are currently in the focus of research addressing the required flexibility. These systems which consist of modular production and logistics units offer the possibility to adapt flexibly in volatile conditions within dynamic supply chains. Hence, this work compiles elements for environmental sustainability, which minimize the carbon footprint in the process industry: transformable production systems, the utilization of bio‐based resources, carbon dioxide and renewable energy as well as the application of these elements in decentral production networks. Finally, possible use cases are determined based on the combination of these elements through a multi‐criteria analysis.
Keywords: Industrial and Manufacturing Engineering; Filtration and Separation; Process Chemistry and Technology; Biochemistry; Chemical Engineering (miscellaneous); Bioengineering

Modular Production with Bio‐Based Resources in a Decentral Production Network - Finkbeiner, Marco; Pannok, Maik; Fasel, Henrik; Riese, Julia; Lier, Stefan (Chemie Ingenieur Technik)
Abstract The change in process industry from fossil resources to alternative feedstock is indispensable due to the scarcity of resources and global warming. This leads to new challenges for the production systems. On the market side, rapid innovation is accompanied by shorter product life cycles leading to an increasing uncertainty of demand in terms of product type, volume and location. Therefore, the following five elements are combined into a concept to address these challenges: transformable production systems, local bio‐based resources, CO 2 as feedstock, renewable energy and decentral production network with local economies.
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Comparison of the Operating Range of a Wetted‐Wall Column with a Packed Column for Distillation - Reitze, Arnulf; Grünewald, Marcus; Riese, Julia (Chemie Ingenieur Technik)
Abstract In this paper, a newly designed distillation column consisting of a wetted wall with a rectangular cross section is analyzed and compared with a conventional packed column with regard to the operating range of both apparatuses. As expected, the pressure drop is considerably lower in the wetted‐wall column and, therefore, it offers a higher range of operation. However, in the wetted‐wall column, the separation efficiency decreases rapidly with increasing F factors. This effect can be overcome by the serial connection of two wetted‐wall columns.
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

New Column Design to Enhance Flexibility: Concept for Hydrodynamic Characterization - Fasel, Henrik; Grünewald, Marcus; Riese, Julia (Chemie Ingenieur Technik)
Abstract This study presents a new and innovative sieve tray design for a more flexible operation of separation columns in terms of possible throughput. The advantage of this new tray design is to ensure an optimal operation for varying feed flow rates and constant separation efficiencies for different load ranges. The aim of this work is to give a short introduction and an outlook to the investigation of the functionality of the designed trays. Moreover, the general design of the new trays, first results for CFD simulations of the dry pressure drop and the experimental setup are presented.
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Flexibility of Power‐to‐Gas Plants: A Case Study - Herrmann, Felix; Grünewald, Marcus; Riese, Julia (Chemie Ingenieur Technik)
Abstract Due to the increasing share of renewable energies in the power sector, the need for energy storage and flexible performance is rising. This study provides an in‐depth investigation of the flexibility of a Power‐to‐Gas plant for the production of synthetic natural gas. Model‐based analysis is conducted for the individual technologies PEM electrolysis, MEA absorption and fixed‐bed methanation as well as for the continuously operated process. This study reveals that the Power‐to‐Gas plant offers a capacity flexibility of 87–125 %, corresponding to 4.79–6.88 MW electrical input power.
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Challenges and Opportunities to Enhance Flexibility in Design and Operation of Chemical Processes - Riese, Julia; Grünewald, Marcus (Chemie Ingenieur Technik)
Abstract Flexibility receives increased interest in chemical engineering and is discussed as one measure to deal with upcoming challenges for the chemical industry. In this paper, different types of flexibility are presented, and flexibility needs are illustrated. The focus is on the evaluation and classification of available solutions to enhance flexibility. Solutions and future challenges across all length scales of chemical engineering are discussed: from tailored catalyst properties to decoupling of processes by means of storage.
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Analysis of Capacity Potentials in Continuously Operated Chemical Processes - Bruns, Bastian; Grünewald, Marcus; Riese, Julia (Chemie Ingenieur Technik)
Abstract A method is proposed to evaluate capacity potentials in continuously operated chemical processes. In the main part of the analysis, the operating windows of the equipment are examined based on detailed steady‐state simulations. The method is applied to a case study of the production process of ethylene oxide as a large‐scale commodity chemical. Results show the limitations continuously operated processes are confronted with. However, opportunities to enlarge or shift the operating window of apparatuses applied are determined.
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Behavior of tall masonry chimneys under wind loadings using CFD technique - Dawood, Abbas O.; Al-Lami, Abbas Jarullah Sangoor; Al-Rkaby, Alaa H.J. (Case Studies in Construction Materials)

Digital Innovation at a Large Energy Enterprise. Talk - Schlüter, Alexander; M. Garbuzova-Schlifter, Maria; Fecher, Florian

Intrapreneuers vs Start-ups - who really creates Innovations? Panel discussion - Schlüter, Alexander

Digitalizing the Planning of our Grids. Talk - Schlüter, Alexander

Untersuchung eines neuen thermischen Partikelverrundungsprozesses - Tissen, Anton; Ponusamy, SathishKumar

Computer- und informationsbezogene Kompetenzen von Schülerinnen und Schülern im internationalen Vergleich - Eickelmann, Birgit; Drossel, Kerstin; Labusch, Amelie; Vennemann, Mario; Casamassima, Gianna (ICILS 2018 #NRW. Vertiefende Analysen und Befunde für Nordrhein-Westfalen im internationalen Vergleich)

Computer- und informationsbezogene Kompetenzen von Schülerinnen und Schülern im internationalen Vergleich - Eickelmann, Birgit; Drossel, Kerstin; Labusch, Amelie; Vennemann, Mario; Casamassima, Gianna (ICILS 2018 #NRW. Vertiefende Analysen und Befunde für Nordrhein-Westfalen im internationalen Vergleich)

ICT usage across Europe: A literature review and an overview of existing data - Ayllón, Sara; Barbovschi, Monica; Casamassima, Gianna; Drossel, Kerstin; Eickelmann, Birgit; Ghețău, Cosmin; Haragus, Teo Paul; Holmarsdottir, Halla Bjork; Hyggen, Christer; Kapella, Olaf; Karatzogianni, Athina; Lado, Samuel; et al.

Überlegungen auf dem Weg zu einer Theorie lehrbezogenen Wandels an Hochschulen - Jenert, Tobias (Zeitschrift für Hochschulentwicklung)

Studien- und Lehrentwicklung als Überwindung institutioneller Grenzziehungen. Eine Netzwerktheoretische Betrachtung. - Jenert, Tobias; Sänger, Niklas (LERNEN im Hochschulzusammenhang)

Die Rolle von sozialen Netzwerken für die Lehrentwicklung und Lehrinnovation an Hochschulen - Sänger, Niklas

Modeling of a Latent Heat Storage System Consisting of Encapsulated PCM- Elements - Grabo, Matti; Acar, Emre; Kenig, Eugeny

MANUFACTURING OF HYBRID COMPONENTS BY VARTM-PROCESS USING NEW SEALING TECHNIQUE DEVELOPED - Chalicheemalapalli Jayasankar, Deviprasad; Stallmeister, Tim; Wang, Zheng; Tröster, Thomas (Hybrid 2020 Materials and Structures)

Semantic Technologies for Situation Awareness - Baader, Franz; Borgwardt, Stefan; Koopmann, Patrick; Thost, Veronika; Turhan, Anni-Yasmin (Künstliche Intell.)

Give Inconsistency a Chance: Semantics for Ontology-Mediated Verification - Dubslaff, Clemens; Koopmann, Patrick; Turhan, Anni-Yasmin (Proceedings of the 33rd International Workshop on Description Logics {(DL} 2020) co-located with the 17th International Conference on Principles of Knowledge Representation and Reasoning {(KR} 2020), Online Event [Rhodes, Greece], September 12th to 14th, 2020)

Professional Development of Vocational Teachers in Language-Sensitive Content Teaching–A Study Visit Abroad as Design-Based Research Intervention for Vocational Teachers Working in School-to-Work Transition Phases - Peitz, Nina-Madeleine

„Sprachliche Barrieren als Herausforderung bei der Integration von Seiteneinsteiger_innen in das Berufskolleg“ – Lehrer_innenbildung im Spiegel des Integrations- und Inklusionsdiskurses - Büttner, Denise; Gürsoy, Erkan (Inklusion in der Lehrerbildung für das berufliche Schulwesen. Beiträge zur Professionalisierung in der ersten Phase der Lehramtsausbildung)

Migration und Mehrsprachigkeit zum Unterrichtsthema machen – Migrationsliteratur als Zugang im Deutschunterricht? - Büttner, Denise; Roll, Heike (ProDaz-Journal)

Finite element error analysis of wave equations with dynamic boundary conditions: L2 estimates - Hipp, David; Kovács, Balázs (IMA Journal of Numerical Analysis)
Abstract $L^2$ norm error estimates of semi- and full discretizations of wave equations with dynamic boundary conditions, using bulk–surface finite elements and Runge–Kutta methods, are studied. The analysis rests on an abstract formulation and error estimates, via energy techniques, within this abstract setting. Four prototypical linear wave equations with dynamic boundary conditions are analysed, which fit into the abstract framework. For problems with velocity terms or with acoustic boundary conditions we prove surprising results: for such problems the spatial convergence order is shown to be less than 2. These can also be observed in the presented numerical experiments.
Keywords: Applied Mathematics; Computational Mathematics; General Mathematics

Finite element error analysis of wave equations with dynamic boundary conditions: L2 estimates - Hipp, David; Kovács, Balázs (IMA Journal of Numerical Analysis)
Abstract $L^2$ norm error estimates of semi- and full discretizations of wave equations with dynamic boundary conditions, using bulk–surface finite elements and Runge–Kutta methods, are studied. The analysis rests on an abstract formulation and error estimates, via energy techniques, within this abstract setting. Four prototypical linear wave equations with dynamic boundary conditions are analysed, which fit into the abstract framework. For problems with velocity terms or with acoustic boundary conditions we prove surprising results: for such problems the spatial convergence order is shown to be less than 2. These can also be observed in the presented numerical experiments.
Keywords: Applied Mathematics; Computational Mathematics; General Mathematics

Higher-order linearly implicit full discretization of the Landau–Lifshitz–Gilbert equation - Akrivis, Georgios; Feischl, Michael; Kovács, Balázs; Lubich, Christian (Mathematics of Computation)
Keywords: Applied Mathematics; Computational Mathematics; Algebra and Number Theory

A convergent algorithm for forced mean curvature flow driven by diffusion on the surface - Kovács, Balázs; Li, Buyang; Lubich, Christian (Interfaces and Free Boundaries)
Keywords: Applied Mathematics

RBF-based penalized least-squares approximation of noisy scattered data on the sphere - Hesse, Kerstin (Multivariate Algorithms and Information-Based Complexity)

Improper Gaussian Signaling for the $K$-User MIMO Interference Channels With Hardware Impairments - Soleymani, Mohammad; Santamaria, Ignacio; Schreier, Peter J. (IEEE Transactions on Vehicular Technology)
Keywords: Electrical and Electronic Engineering; Computer Networks and Communications; Aerospace Engineering; Automotive Engineering

Rate Region of the K-user MIMO Interference Channel with Imperfect Transmitters - Soleymani, Mohammad; Santamaria, Ignacio; Maham, Behrouz; Schreier, Peter J. (2020 28th European Signal Processing Conference (EUSIPCO))

DeepWind: An Accurate Wind Turbine Condition Monitoring Framework via Deep Learning on Embedded Platforms - Mohammadi, Hassan Ghasemzadeh; Arshad, Rahil; Rautmare, Sneha; Manjunatha, Suraj; Kuschel, Maurice; Jentzsch, Felix Paul; Platzner, Marco; Boschmann, Alexander; Schollbach, Dirk (2020 25th IEEE International Conference on Emerging Technologies and Factory Automation (ETFA))

Approaching Critical Decay in a Strongly Degenerate Parabolic Equation - Winkler, Michael (Journal of Dynamics and Differential Equations)
Abstract The Cauchy problem in $${\mathbb {R}}^n$$ R n , $$n\ge 1$$ n ≥ 1 , for the parabolic equation $$\begin{aligned} u_t=u^p \Delta u \qquad \qquad (\star ) \end{aligned}$$ u t = u p Δ u ( ⋆ ) is considered in the strongly degenerate regime $$p\ge 1$$ p ≥ 1 . The focus is firstly on the case of positive continuous and bounded initial data, in which it is known that a minimal positive classical solution exists, and that this solution satisfies $$\begin{aligned} t^\frac{1}{p}\Vert u(\cdot ,t)\Vert _{L^\infty ({\mathbb {R}}^n)} \rightarrow \infty \quad \hbox {as } t\rightarrow \infty . \end{aligned}$$ t 1 p ‖ u ( · , t ) ‖ L ∞ ( R n ) → ∞ as t → ∞ . The first result of this study complements this by asserting that given any positive $$f\in C^0([0,\infty ))$$ f ∈ C 0 ( [ 0 , ∞ ) ) fulfilling $$f(t)\rightarrow +\infty $$ f ( t ) → + ∞ as $$t\rightarrow \infty $$ t → ∞ one can find a positive nondecreasing function $$\phi \in C^0([0,\infty ))$$ ϕ ∈ C 0 ( [ 0 , ∞ ) ) such that whenever $$u_0\in C^0({\mathbb {R}}^n)$$ u 0 ∈ C 0 ( R n ) is radially symmetric with $$0< u_0 < \phi (|\cdot |)$$ 0 < u 0 < ϕ ( | · | ) , the corresponding minimal solution u satisfies $$\begin{aligned} \frac{t^\frac{1}{p}\Vert u(\cdot ,t)\Vert _{L^\infty ({\mathbb {R}}^n)}}{f(t)} \rightarrow 0 \quad \hbox {as } t\rightarrow \infty . \end{aligned}$$ t 1 p ‖ u ( · , t ) ‖ L ∞ ( R n ) f ( t ) → 0 as t → ∞ . Secondly, ( $$\star $$ ⋆ ) is considered along with initial conditions involving nonnegative but not necessarily strictly positive bounded and continuous initial data $$u_0$$ u 0 . It is shown that if the connected components of $$\{u_0>0\}$$ { u 0 > 0 } comply with a condition reflecting some uniform boundedness property, then a corresponding uniquely determined continuous weak solution to ( $$\star $$ ⋆ ) satisfies $$\begin{aligned} 0< \liminf _{t\rightarrow \infty } \Big \{ t^\frac{1}{p} \Vert u(\cdot ,t)\Vert _{L^\infty ({\mathbb {R}}^n)} \Big \} \le \limsup _{t\rightarrow \infty } \Big \{ t^\frac{1}{p} \Vert u(\cdot ,t)\Vert _{L^\infty ({\mathbb {R}}^n)} \Big \} <\infty . \end{aligned}$$ 0 < lim inf t → ∞ { t 1 p ‖ u ( · , t ) ‖ L ∞ ( R n ) } ≤ lim sup t → ∞ { t 1 p ‖ u ( · , t ) ‖ L ∞ ( R n ) } < ∞ . Under a somewhat complementary hypothesis, particularly fulfilled if $$\{u_0>0\}$$ { u 0 > 0 } contains components with arbitrarily small principal eigenvalues of the associated Dirichlet Laplacian, it is finally seen that (0.1) continues to hold also for such not everywhere positive weak solutions.
Keywords: Analysis

Pollicott-Ruelle Resonant States and Betti Numbers - Küster, Benjamin; Weich, Tobias (Communications in Mathematical Physics)
Abstract Given a closed orientable hyperbolic manifold of dimension $$\ne 3$$ ≠ 3 we prove that the multiplicity of the Pollicott-Ruelle resonance of the geodesic flow on perpendicular one-forms at zero agrees with the first Betti number of the manifold. Additionally, we prove that this equality is stable under small perturbations of the Riemannian metric and simultaneous small perturbations of the geodesic vector field within the class of contact vector fields. For more general perturbations we get bounds on the multiplicity of the resonance zero on all one-forms in terms of the first and zeroth Betti numbers. Furthermore, we identify for hyperbolic manifolds further resonance spaces whose multiplicities are given by higher Betti numbers.
Keywords: Mathematical Physics; Statistical and Nonlinear Physics

Fallportraits von Bielefelder Grundschulkindern. Fallarbeit in der (phasenübergreifenden) Lehrer_innenbildung - Pieper, Catania; Kottmann, Brigitte; Miller, Susanne (HLZ - Herausforderung Lehrer_innenbildung, Zeitschrift zur Konzeption, Gestaltung und Diskussion)
In dem vorliegenden Beitrag werden insgesamt zehn authentische Fallportraits von Bielefelder Grundschulkindern vorgestellt. Sie bieten sowohl Einblicke in die familiäre als auch in die schulische Situation von Kindern, so dass heterogene Lebenswirklichkeiten mehrperspektivisch abgebildet werden. Die Fallportraits können im Rahmen der phasenübergreifenden Lehrer_innenbilung eingesetzt werden, um bspw. Transferprozesse zwischen Theorie und Praxis zu unterstützen, eine kritisch-reflexive Auseinandersetzung sowie ein Sensibilisieren für heterogene Lebenswirklichkeiten zu fördern, etc. Didaktische Implementierungsmöglichkeiten und Anknüpfungspunkte zur Portfolioarbeit (2), vier exemplarische theoretische Schwerpunkte (3) sowie der Prozess der Fallportraitgenerierung (4) werden zunächst im vorliegenden Beitrag erläutert, ehe die zehn Fallportraits (5), ein Fazit (6) und zwei exemplarische Veranschaulichungsmaterialien (7) den Beitrag beenden.

Die Simulation der Pandemie..Ein Beitrag zur Reihe "Sicherheit in der Krise". - Hälterlein, Jens

Die curriculare Entwicklung der Anforderungen von anwendungsbezogenen Aufgaben - Malik, Sara Naseem (Beiträge zum Mathematikunterricht 2020. 54. Jahrestagung der Gesellschaft für Didaktik der Mathematik vom 09. bis 13. März 2020 in Würzburg)

Im Schweigen der Klänge. Zu Farzia Fallahs Sextett "im selben augenblick" (2018) - Ricke, Anna (MusikTexte)

Tax avoidance through securitization - Uhde, André (The Quarterly Review of Economics and Finance)
Employing a unique hand-collected sample of 956 credit risk securitization transactions issued by 64 stock-listed European banks across the EU-13 plus Switzerland over the period from 1997 to 2010, this paper empirically analyzes the impact of securitization on the issuing banks’ effective tax rates. Our analysis reveals that banks may reduce their tax expense through securitization via a direct and indirect channel suggesting that tax avoidance may be a further motive for banks to engage in the securitization business. These baseline findings remain robust under various robustness checks, especially when implementing structural equation models and controlling for a reverse causality between the banks’ tax burden and their incentive to securitize. Finally, various sensitivity analyses provide further important results and implications for tax policies, banking regulation and the ongoing process of revitalizing the European securitization market.
Keywords: Securitization; Credit risk transfer; Effective tax rates; European banking

Tax avoidance through securitization - Uhde, André (The Quarterly Review of Economics and Finance)
Employing a unique hand-collected sample of 956 credit risk securitization transactions issued by 64 stock-listed European banks across the EU-13 plus Switzerland over the period from 1997 to 2010, this paper empirically analyzes the impact of securitization on the issuing banks’ effective tax rates. Our analysis reveals that banks may reduce their tax expense through securitization via a direct and indirect channel suggesting that tax avoidance may be a further motive for banks to engage in the securitization business. These baseline findings remain robust under various robustness checks, especially when implementing structural equation models and controlling for a reverse causality between the banks’ tax burden and their incentive to securitize. Finally, various sensitivity analyses provide further important results and implications for tax policies, banking regulation and the ongoing process of revitalizing the European securitization market.
Keywords: Securitization; credit risk transfer; effective tax rates; European banking

Multiprofessionelle Teamarbeit (MPT) im Kontext einer Dualität des Sozialen. Eine rekonstruktive Mehrebenenanalyse am Berufskolleg vor dem Hintergrund inklusiver Bildung. - Kückmann, Marie-Ann

Schulbücher. Werkzeuge zum Üben in den Fächern Deutsch und Mathematik - Rezat, Sara; Rezat, Sebastian (Die Grundschulzeitschrift 320)

Rekonstruktion diagrammatischen Schließens beim Erlernen der Subtraktion negativer Zahlen - Schumacher, Jan; Rezat, Sebastian (Zeichen und Sprache im Mathematikunterricht: Semiotik in Theorie und Praxis)

Mathematiklernen mit digitalen Schulbüchern im Spannungsfeld zwischen Individualisierung und Kooperation - Rezat, Sebastian (Mobile Medien im Schulkontext)

Differenziertes Üben gestalten. Zwischen Umsetzung in der Praxis und Fundierung in der Forschung. - Leuders, Timo; Wessel, Lena (Pädagogik 2/2020)

Sprachbildender Vorstellungsaufbau für verschiedene mathematische Konzepte: Brüche in Klasse 6 - Wessel, Lena; Kuzu, T.; Prediger, Susanne (Sprachbildender Mathematikunterricht in der Sekundarstufe - ein forschungsbasiertes Praxisbuch)

Fach- und sprachintegrierte Ansätze für Neuzugewanderte - Sprütten, F.; Wessel, Lena; Zentgraf, K.; Prediger, S. (Sprachbildender Mathematikunterricht in der Sekundarstufe. Ein forschungsbasiertes Praxisbuch)

Language for Mathematics in Vocational Contexts. Handbook for teachers and facilitators - Wessel, Lena; Prediger, S.; Stein, A.; Wijers, M.; Jonker, V.

University Mathematics Didactic Research on Number Theory, Algebra, Discrete Mathematics, Logic - Biehler, Rolf; Durand-Guerrier, Viviane (Proceedings of the Third Conference of the International Network for Didactic Research in University Mathematics (INDRUM 2020, 12-19 September 2020))
Keywords: Number Theory; Algebra; Discrete Mathematics; Logic; Research in University Mathematics Edcuation

Motivation of out-of-field teachers for participating in professional development courses in mathematics - Lünne, Steffen; Schnell, Susanne; Biehler, Rolf (European Journal of Teacher Education)
Keywords: Education

Theory-Based Design of Professional Development for Upper Secondary Teachers–Focusing on the Content-Specific Use of Digital Tools - Barzel, Bärbel; Biehler, Rolf (Professional development and knowledge of mathematics teachers)

Students’ Understanding of the Derivative Concept in the Context of Mathematics for Economics - Feudel, Frank; Biehler, Rolf (Journal für Mathematik-Didaktik)
Abstract The derivative concept plays a major role in economics. However, its use in economics is very heterogeneous, sometimes inconsistent, and contradicts students’ prior knowledge from school. This applies in particular to the common economic interpretation of the derivative as the amount of change while increasing the production by one unit. Hence, in calculus courses for economics students, learners should acquire an understanding of the derivative that is mathematically acceptable and connected to their prior knowledge, but which also takes into account its practical use in economics. In this paper we first develop a theoretical model describing such an understanding of the derivative for economics students. We then present an exploratory study investigating the extent to which economics students have such an understanding after their calculus course. The results indicate that many of them might not have acquired this kind of understanding, in particular concerning the common economic interpretation of the derivative. The study furthermore yields possible gaps in students’ understanding and possible misconceptions.
Keywords: Education; General Mathematics

Using Figurate Numbers in Elementary Number Theory – Discussing a ‘Useful’ Heuristic From the Perspectives of Semiotics and Cognitive Psychology - Kempen, Leander; Biehler, Rolf (Frontiers in Psychology)
Keywords: General Psychology

Was verstehen Schülerinnen und Schüler unter „Beweis“? – ausgewählte Ergebnisse einer Pilotstudie - Kempen, Leander; Krämer, Sandra; Biehler, Rolf (Beiträge zum Mathematikunterricht 2020)

Hochschuldidaktik Mathematik: Fachbezogenes Design und empirische Studien - Biehler, Rolf; Kempen, Leander; Paravicini, Walther (Beiträge zum Mathematikunterricht 2020)

Automatisierte Entscheidungsverfahren als Thema im allgemeinbildenden Mathematikunterricht - Fleischer, Yannik; Biehler, Rolf (Beiträge zum Mathematikunterricht 2020)

Frei verfügbare Materialien für Unterricht und Fortbildung: Stochastik verständnisorientiert unterrichten - Griese, Birgit; Nieszporek, Ralf; Biehler, Rolf (Stochastik in der Schule)

Ffunt@OWL – Konzept und Gestaltungsprinzipien zur Qualifizierung fachfremd Mathematik unterrichtender Lehrkräfte der Sekundarstufe I - Lünne, Steffen; Schnell, Susanne; Biehler, Rolf (Professionelles Handeln im fachfremd erteilten Mathematikunterricht)

“I only know the absolute value function”–About students’ concept images and example spaces concerning continuity and differentiability - Lankeit, Elisa; Biehler, Rolf (Proceedings of the Third Conference of the International Network for Didactic Research in University Mathematics (INDRUM 2020, 12-19 September 2020))

Investigating high school graduates’ personal meaning of the notion of “mathematical proof” - Kempen, Leander; Krämer, Sandra; Biehler, Rolf (Proceedings of the Third Conference of the International Network for Didactic Research in University Mathematics (INDRUM 2020, 12-19 September 2020))

Votingfragen in den Übungen zur Analysis – Wirkung verschiedener Einsatzszenarien - Lankeit, Elisa; Bauer, T.; Biehler, Rolf (Beiträge zum Mathematikunterricht 2020)

Mathematics learning support centres in Germany—an overview - Schürmann, Mirko; Gildehaus, Lara; Liebendörfer, Michael; Schaper, Niclas; Biehler, Rolf; Hochmuth, Reinhard; Kuklinski, Christiane; Lankeit, Elisa (Teaching Mathematics and its Applications: An International Journal of the IMA)
Abstract Mathematics learning support centres (MLSC) are widely established and evaluated in English-speaking countries (such as the UK, Ireland and Australia). In most of these countries, several national surveys on MLSCs exist. They give an overview of the number of MLSCs as well as their characteristics in these countries. In Germany, there is a lack of studies on MLSCs and the landscape of MLSCs has not been described yet. This article presents basic information concerning counts of MLSCs and their characteristics at universities. Based on a three-step approach of analysing university homepages and additional personal contact via email or phone calls, we gathered typical MLSC features (e.g. staff quantities and qualification, opening and support hours, supported study programmes). We analysed 190 universities from a web-based register on study programmes. In total, we found 61 MLSCs located at 51 German universities. Another 16 support centres were specialized on mathematics didactics, which means they focussed on didactical and methodological support for preservice teacher students and often provided different teaching materials. Thirty-eight centres were located at universities (62.3%) and 23 MLSCs at universities of applied sciences and comparable universities (37.7%). The MLSCs were different in their sizes of staff and opening hours, and both the numbers of staff and the service hours differed greatly. The student groups MLSCs at German universities focus on differ concerning characteristics like study programme or semester. We will provide the main categories describing these groups. We seek to answer research questions concerning the characteristics of MLSCs in Germany and discuss the results compared to international findings. This information is useful for further international collaborative research, for example a standardized international survey. From a national perspective, these findings support networking and collaborations between the MLSCs as well. As some German MLSCs are facing financial cuts, these results might help in gaining additional funding.
Keywords: Education; General Mathematics

The role of learning strategies for performance in mathematics courses for engineers - Liebendörfer, Michael; Göller, Robin; Gildehaus, Lara; Kortemeyer, Jörg; Biehler, Rolf; Hochmuth, Reinhard; Ostsieker, Laura; Rode, Jana; Schaper, Niclas (Proceedings of the Third Conference of the International Network for Didactic Research in University Mathematics (INDRUM 2020, 12-19 September 2020))

studiVEMINTvideos – Mathematische Lernvideos zur Studienvorbereitung und Unterstützung im ersten Studienjahr - Biehler, Rolf; Liebendörfer, Michael; Schmitz, Angela; Fleischmann, Yael; Krämer, Sandra; Ostsieker, Laura; Schlüter, Sarah (Beiträge zum Mathematikunterricht 2020)

Data science education in secondary schools: Teaching and learning decision trees with CODAP and Jupyter Notebooks as an example of integrating machine learning into statistics education - Biehler, Rolf; Fleischer, Yannik; Budde, Lea; Frischemeier, Daniel; Gerstenberger, Dietrich; Podworny, Susanne; Schulte, Carsten (New Skills in the Changing World of Statistics Education Proceedings of the Roundtable conference of the International Association for Statistical Education (IASE))

Data Science Education in Secondary School: How to Develop Statistical Reasoning When Exploring Data Using CODAP - Budde, Lea; Frischemeier, Daniel; Biehler, Rolf; Fleischer, Yannik; Gerstenberger, Dietrich; Podworny, Susanne; Schulte, Carsten (New Skills in the Changing World of Statistics Education: Proceedings of the Roundtable conference of the International Association for Statistical Education (IASE), July 2020)

Seven Paradoxes of Business Process Management in a Hyper-Connected World - Beverungen, Daniel; Buijs, Joos C. A. M.; Becker, Jörg; Di Ciccio, Claudio; van der Aalst, Wil M. P.; Bartelheimer, Christian; vom Brocke, Jan; Comuzzi, Marco; Kraume, Karsten; Leopold, Henrik; Matzner, Martin; Mendling, Jan; et al. (Business & Information Systems Engineering)
Business Process Management is a boundary-spanning discipline that aligns operational capabilities and technology to design and manage business processes. The Digital Transformation has enabled human actors, information systems, and smart products to interact with each other via multiple digital channels. The emergence of this hyper-connected world greatly leverages the prospects of business processes – but also boosts their complexity to a new level. We need to discuss how the BPM discipline can find new ways for identifying, analyzing, designing, implementing, executing, and monitoring business processes. In this research note, selected transformative trends are explored and their impact on current theories and IT artifacts in the BPM discipline is discussed to stimulate transformative thinking and prospective research in this field.
Keywords: Business process management (BPM); Social computing; Smart devices; Big data analytics; Real-time computing; BPM life-cycle

Tax Administrative Burden, Tax Relief and Investment during the Corona Crisis - Heile, Vanessa; Huber, Hans-Peter; Maiterth, Ralf; Sureth-Sloane, Caren

Populäre Kultur - Janus, Richard (Das Wissenschaftlich-Religionspädagogisches Lexikon im Internet)

Kompetenz- und professionsorientierte Didaktik. Grundform des Theologiestudiums - Reis, Oliver (Pfarrer oder Pfarrerin werden und sein. Herausforderungen für Beruf und theologische Bildung in Studium, Vikariat und Fortbildung)

Pirker, Viera / Juen, Maria: Religion – (k)ein Fach wie jedes andere. Spannungsfelder und Perspektiven in der kompetenzorientierten Leistungsbeurteilung. Stuttgart: Kohlhammer 2018 - Reis, Oliver (Theologischer Revue)

Grümme, Bernhard: Religionspädagogische Denkformen. Eine kritische Revision im Kontext von Heterogenität. Freiburg i.Br.: Verlag Herder 2019 - Reis, Oliver (Theologische Literaturzeitung)

Lernortspezifische Jugendtheologie als Marker religionspädagogischer Grundlage – ein Tagungsprotokoll - Reis, Oliver („Weil man halt ja nebenbei, so etwas gelernt hat…“. Lernortspezifische Jugendtheologie in Schule und Gemeinde)

Die Bibel als Medium religiöser Sprachentwicklung - Reis, Oliver; Lenze, Alina; Nagels, Johanna; Potthast, Fabian (Religion lernen. Jahrbuch für konstruktivistische Religionsdidaktik)

Machtvolle Differenzierungen: Wie Inklusionsdiskurse (religions-)pädagogische Praxis prägen - Brandstetter, Bettina; Reis, Oliver (Inklusive Religionspädagogik der Vielfalt. Konzeptionelle Grundlagen und didaktische Konkretionen)